Comparative performance of carbon nanotube and nanoclay on thermal properties and flammability behavior of amorphous polyamide/SEBS blend. Issue 6 (1st April 2020) - Paes, Letícia Helena Gasparini; Steffen, Teresa Tromm; Becker, Daniela
Abstract: Multiwall carbon nanotubes (CNT) or montmorillonite clay (MMT‐30B) were added to a poly(hexamethylene isophthalamide‐co‐terephthalamine) (an amorphous polyamide ‐ aPA) and styrene‐ethylene/butylene‐styrene graphitized with maleic anhydride (SEBS) blend, in different concentrations, in order to investigate the morphology, thermal properties and flammability behavior. Different nanoparticle localizations in the phase blend were observed through transmission electronic microscopy. CNT nanoparticles are localized in SEBS phase, and MMT‐30B nanoparticles in aPA phase. No significant changes were observed on transition temperatures and thermal stability with both nanoparticle additions. However, a slight increase on storage modulus for clay nanocomposites and a slight reduction for carbon nanotube nanocomposites were observed, due to their different phase localizations. Regarding flammability, CNT nanocomposites showed better performance as a flame retardant when compared to samples with MMT‐30B. Although the MMT‐30B nanocomposites could not be classified according to the UL‐94 criteria, no dripped flaming particles were observed, due to the a char barrier formation on the polymer surface. The CNT nanocomposites were classified according to the UL‐94 criteria as V‐2. The CNT's selective localization on the SEBS phase decreases its heat‐release rate, but no interconnected network structure was formed in the matrix to suppress the dripping flaming particles.